Comparative study of quality practices between Japanese and non-Japanese based electrical and electronics companies in Malaysia: a survey - Ahmad, Md. Fauzi; Mohd. Yusof, Sha'ri; Mohd. Yusof, Noordin (Penerbit UTM Press, 2007)
This paper presents the results of a study on the comparison of quality practices between Japanese and non-Japanese companies in Malaysia. The main objective is to investigate the differences that may exist between them in implementing quality management. Towards that end, a questionnaire was developed, validated and sent out to 370 companies in the electrical and electronics sector and the survey gave a response rate of 21.9 per cent. The results show that Japanese companies have higher levels of quality activities when compared to non-Japanese companies. The top five quality activities with big gap against non-Japanese companies are; quality control circle, supplier improvement, application of Failure Mode and Effect Analysis (FMEA), conducting Value Engineering (VE) and implementing quality costing. ISO 9001 was found to be the most useful practice in all the companies surveyed. The results also showed that in-process inspection, 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) activities, internal quality audit and conducting production planning and control have high practice level in all companies. The findings of this research points to the need for much greater emphasis on quality practices found lacking by non-Japanese companies in their future quality improvement efforts